Two new species of Prionospio (Annelida: Spionidae) from the Northwest and Northeast Atlantic - Delgado-Blas, Víctor Hugo; Peraza, Russell Giovanni Uc (Zootaxa, 2024)
Specimens of Prionospio collected from the Northeastern Atlantic Ocean (“Gay Head-Bermuda Transect”) and North Sea (Sweden), and identified as Prionospio dubia, were examined, and two new species were described: P. gayheadia sp. nov. and P. multisetosa sp. nov. P. gayheadia sp. nov., is characterized by having a flask-shaped prostomium, anteriorly truncate and no eyes; the first and fourth pairs of branchiae with long, naked, smooth distal tips; very short, rounded first neuropodial postchaetal lamellae, much smaller than 1/5 of the size of the notopodial lamellae; oval neuropodial postchaetal lamellae on chaetiger 3; sabre chaetae from chaetigers 15–18; notopodial hooded hooks from chaetigers 70–76 (smaller specimens 56–59), all hooded hooks with four pairs of accessory teeth. P. multisetosa sp. nov. has a skittle-shaped prostomium, anteriorly rounded and no eyes; the first and four pairs of branchiae with very short, naked, smooth distal tips; well- developed notopodial prechaetal lamellae on chaetigers 13–33; first neuropodial postchaetal lamellae large, tongue-shaped, slightly smaller than the notopodial lamellae; neuropodial postchaetal lamellae on chaetiger 3 subtriangular (sometimes with rectangular lamellae to the left or right); sabre chaetae from chaetigers 19–24; notopodial hooded hooks from chaetigers 50–55 (smaller specimen 46), all hooded hooks with three pairs of small teeth. An identification key and comparison table detailing the most relevant characters of the species most similar to P. dubia are provided.